Seasonal and individual variation of semen quality parameters in crossbred (Alpine x Beetal) buck - NARWADE, B. M.; MOHANTY, TUSHAR KUMAR; BHAKAT, MUKESH; RAHIM, ABDUL (Indian Journal of Dairy Science, 2018)
Present investigation was conducted on five crossbred buck to assess individual performance and seasonal effect on semen quality parameters. Semen was collected twice a week using artificial vagina and evaluated for its physical characteristics. Data on 625 ejaculates from five adult bucks (125×5) during different season were recorded and analyzed for semen quality parameters. The overall mean ejaculate volume, mass activity (MA), progressive motility, live sperm, sperm concentration, hypo-osmotic swelling test (HOST) and intact acrosome were 1.09±0.01ml, 3.29±0.03%, 76.46±0.31%, 78.65±0.21% 2.97´109/ml, 69.31±0.21% and 93.89±0.09%, respectively. Analysis revealed that, buck had significant (p<0.05) effect on all semen quality parameters except sperm concentration. Season has also significant (p<0.05) effect on all semen quality parameters. Ejaculates volume was significantly (p<0.05) lower in winter season and higher in hot-dry summer. However, other parameters like mass activity (MA), progressive motility, live percent, sperm concentration and HOST percent were significantly (p<0.05) higher in winter season and lower during hot-dry summer season. It can be concluded that there is individual variation in semen quality and semen produced during winter season is most suitable for better quality semen in comparison to other seasons in crossbred buck.